Please help, need for math hw and cant figure it out
![Please help need for math hw and cant figure it out class=](https://us-static.z-dn.net/files/da2/de4a2b4d0401c2f7a6cfda148d19f5c4.jpg)
The standard form of the quadratic function f(x) = -3x^2 + 6x - 2 is f(x) = -3x^2 + 6x - 2
The quadratic function is given as
f(x) = -3x^2 + 6x - 2
The standard form of a quadratic function is represented as:
f(x) = ax^2 + bx + c
When both equations are compared, we can see that the function f(x) = -3x^2 + 6x - 2 is already in standard form
Where
a = -3
b = 6
c = -2
Hence, the standard form of the quadratic function f(x) = -3x^2 + 6x - 2 is f(x) = -3x^2 + 6x - 2
Read more about quadratic function at
https://brainly.com/question/25841119
#SPJ1